The Role of Teachers in Strengthening Character as Role Models for Students to Instill the Value of Honesty in the Era of Society 5.0 - Suci Fauziah Rahma; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the role of teachers as role models in strengthening students’ character, particularly in instilling honesty values in the era of Society 5.0, where rapid technological advancement has significantly influenced students’ moral behavior and increased academic dishonesty. This research employed a qualitative approach using library research by reviewing relevant literature, including books, scientific journals, and research articles related to character education, teacher exemplarity, honesty values, and educational challenges in the digital era. The collected data were analyzed descriptively to identify key concepts and theoretical perspectives regarding teachers’ roles as uswah hasanah in character formation. The findings indicate that teachers’ exemplary behavior plays a crucial role in shaping students’ honesty character, reflected through consistency between words and actions, fairness in assessment, openness in communication, responsibility, and ethical use of technology in learning activities. Through continuous role modeling, teachers enable students to internalize honesty values not merely as theoretical concepts but as practical attitudes applied in daily academic life. However, teachers also face various challenges, including the influence of digital culture, external environmental factors, limited instructional time, and the dominance of instant oriented academic practices. Therefore, strengthening teachers’ awareness, professionalism, and moral commitment is essential to ensure the effectiveness of honesty character development in contemporary educational settings. This study provides conceptual insights into strengthening honesty character through teacher exemplarity and contributes to the development of character education strategies that integrate moral values with technological advancement in the Society 5.0 era.